2020
DOI: 10.1016/j.ihj.2020.07.014
|View full text |Cite
|
Sign up to set email alerts
|

Study of correlation between epicardial fat thickness and severity of coronary artery disease

Abstract: Epicardial fat thickness (EFT) reflects visceral adiposity and is associated with coronary artery disease (CAD). This study aimed to assess the correlation of echocardiographic EFT with the severity of CAD and to determine the EFT cut-off to predict CAD. EFT was measured in 503 patients undergoing coronary angiogram. Mean EFT was significantly higher in the CAD group than control group (5.55 ± 1.21 mm vs 3.25 ± 1.15 mm, p < 0.0001). EFT correlated with Gensini score (r = 0.906, p < 0.001). EFT cut-off ≥ 4.75 m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 14 publications
(16 reference statements)
1
5
0
1
Order By: Relevance
“…Also, the EAT mean thickness was found to be statistically significantly higher among those with significant coronary stenosis than those without [7.859 ± 0.691 mm versus 5.600 ± 0.386 mm] (P value < 0.001). This observation is supported by the study of Shambu et al who measured EAT in 503 patients undergoing coronary angiogram and found that mean EAT was significantly higher in the CAD group than the control group (5.55 ± 1.21 mm vs 3.25 ± 1.15 mm, p < 0.0001) [14].…”
Section: Relation Between Eat and Cardiovascular Risksupporting
confidence: 59%
See 2 more Smart Citations
“…Also, the EAT mean thickness was found to be statistically significantly higher among those with significant coronary stenosis than those without [7.859 ± 0.691 mm versus 5.600 ± 0.386 mm] (P value < 0.001). This observation is supported by the study of Shambu et al who measured EAT in 503 patients undergoing coronary angiogram and found that mean EAT was significantly higher in the CAD group than the control group (5.55 ± 1.21 mm vs 3.25 ± 1.15 mm, p < 0.0001) [14].…”
Section: Relation Between Eat and Cardiovascular Risksupporting
confidence: 59%
“…This result was supported by Eroglu et al in 2009 who reported that the best cutoff value of EAT for CAD was 5.2 mm [5]. Also, Shambu et al found that EAT at a cutoff ≥ 4.75 mm had 87% sensitivity and 63% specificity for the prediction of significant CAD [14].…”
Section: Relation Between Eat and Cardiovascular Riskmentioning
confidence: 60%
See 1 more Smart Citation
“…For instance, one study defined the degree of coronary artery stenosis as mild (<50%), moderate (50–69%), and severe (≥70%) [ 30 ]. In other studies, severe stenosis was only considered when coronary angiography showed stenosis in any vessel exceeding 50% [ 31 , 32 , 33 , 34 ], 70% [ 35 , 36 ], or even 75% [ 37 , 38 , 39 , 40 ]. In this study, we found that when any coronary artery stenosis ≥ 50%, obvious symptoms, including chest pain and chest tightness, are recorded.…”
Section: Methodsmentioning
confidence: 99%
“…EAT имеет эндокринные, паракринные, вазокринные и воспалительные эффекты и связана с метаболическим синдромом, инсулинорезистентностью, ИБС и артериальной гипертензией. Следовательно, измерение толщины EAT приобрело большое значение для выявления рисков прогрессирования ССЗ [37][38][39].…”
Section: передовая статья обзоры литературыunclassified